2012
DOI: 10.1111/j.2042-7158.2012.01502.x
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of endothelial nitric oxide synthase and asymmetric dimethylarginine by matrine attenuates isoproterenol-induced acute myocardial injury in rats

Abstract: Our results suggested that matrine protects against isoproterenol-induced myocardial ischaemia via eNOS and ADMA pathway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
25
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 45 publications
5
25
0
Order By: Relevance
“…In this study, matrine was given for the longest duration in comparison to previous reports [28,38], and matrine-treated rats appeared to have a significantly lower mean body weight from week 5 to the end of the experiment. These data raise concerns about the toxicity of matrine.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In this study, matrine was given for the longest duration in comparison to previous reports [28,38], and matrine-treated rats appeared to have a significantly lower mean body weight from week 5 to the end of the experiment. These data raise concerns about the toxicity of matrine.…”
Section: Discussionmentioning
confidence: 98%
“…Our previous studies demonstrated that oral administration of matrine (50 and 100 mg/kg) was beneficial for the prevention of isoproterenol-induced myocardial infarction in rats [28,38], which suggests that matrine may offer advantages in terms of cardiovascular events over COX-2 inhibitors. Lubet et al [6] suggested that most or all of the efficacy of chemopreventive compounds occurs later than the initiation phase in this model.…”
Section: Discussionmentioning
confidence: 99%
“…It is well documented that rats treated with low (0.02-3.0 mg/kg) doses of isoproterenol was a useful model to assess the mechanisms of myocardial growth and the progression of cardiac diseases, 28 whereas subcutaneous injection of very large (20-100 mg/kg) doses of isoproterenol to experiment animals were found to induce subendocardial myocardial ischemia, hypoxia, necrosis, and finally fibroblastic hyperplasia, and the pathophysiological and morphologic alterations in the heart of this noncoronary myocardial necrotic rat model were comparable with those taking place in human myocardial infarction. 21,22,28,29 In our study, acute myocardial injury was induced in rats by subcutaneous injection of 85 mg/kg of isoproterenol daily for two consecutive days, [21][22][23][24]29 and the efficacy of betaine on protecting the heart against myocardial infarction were observed on this noninvasive myocardial necrotic rat model.…”
Section: Discussionmentioning
confidence: 99%
“…[21][22][23] Therefore, the aim of this work was to investigate the cardioprotective effects of betaine on the regulation of the STAT3 and apoptotic pathway.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, ISOinduced myocardial injury serves as a well-standardized model to study the beneficial effects of many drugs [6]. The mechanism of action of ISO has been linked to its ability to deplete the energy reserve of the myocardium and to induce severe oxidative stress, resulting in necrotic lesions in the myocardium [7,8]. Hence, antioxidative agents may play an important role in ameliorating ISO-induced toxicity.…”
Section: Introductionmentioning
confidence: 99%